Shamba Shape Up survey of access and use - Burra, Dharani Dhar; Ramírez Villegas, Julián Armando; Galgallo, Diba; Bhamra, Saranjeet Kaur (2023)
As part of the Livestock and Climate initiative, we have been working together with MediaE to improve the advisories related to climate and financial aspects of agriculture. For instance, we have been developing content on Shamba Shape-Up (SSU) television episodes which is one of the products of MediaE. However, one of the key learnings from developing content is whether the episodes are actionable or not. In this research activity, we want to understand through a survey whether the content of SSU episodes have been useful or not and understand the drivers of what makes the content actionable.